Investigating the health systems of the word\'s armies and providing an appropriate model - Nader Markazi-Moghaddam; Sanaz Zargar Balaye Jame; Saeid Shahraki (فصلنامه ابن سینا)
Background: The military health system of any country has a decisive role in the health of those countries. Every army needs a proper model of health system due to the the role of defense and health. The aim of this study was to conduct a quantitative study based on the opinions of health experts in the Army of the Islamic Republic of Iran. Materials and methods: This qualitative study was conducted from 2018 to 2019. Information on the military health systems of the world was extracted from the Military Health System Website, military interviews, reports, and articles of the military health system from various countries. Then, based on the collected information, a draft semi-structured interview was extracted within the framework of the functions and objectives of the proposed military health system. After preparing the semi-structured interview questions, an interview was prepared from selected health experts of the Armed Forces. The data were coded using Maxqda12 software. Codes were linked to themes and sub-themes within a thematic framework. Results: There were 10 semi-structured interviews with military health experts. After conducting the interviews, coding and categorizing the data, four themes were identified, including incumbency, resource production, and financing as well as service delivery, which together with 23 sub-themes formed the military health system framework. Conclusion: Applying the right model for the health care system of the Armed Forces can create a structure that is appropriate for the country conditions and pave the way for achieving security and health care goals. As a result, it can be a model for other health care systems.